Diversity and Threats of Freshwater Fishes of Yerla River, Northern Western Ghat, Maharashtra, India - Bhoi-Kamble, Angha Vikram; Kumbar, Suresh M (International Journal of Ecology and Environmental Sciences, 2025)
The fish fauna of Yerla River, Sangli district was studied between 2021 to 2024. It is aimed at making a comprehensive checklist and to find out real anthropogenic threats to the fish fauna of Yerla River. A total of twelve species belonging to two orders, five families and eight genera were recorded. Order Cypriniformes were the most dominant one and represents eight species followed by Siluriformes with four species. Among these, three species are endemic to the Western Ghats and one species is endemic to the Krishna River System. As per IUCN’s Red list of Threatened Species, nine species assessed as least concern; two species as endangered and one species as vulnerable. The fish fauna of the river is threatened due to exotic species like Pterygoplichthys pardalis and Pangasianodon hypophthalmus of various sites of Yerla River and some anthropogenic activities like releasing of agricultural effluents, domestic organic wastes and non-degradable plastic materials owing to tourism activities. Since, this small study area hosts four endemic and three threatened species. Therefore, Yerla River will be the most suitable habitat for conservation of endemic and threatened species.